Evaluation of cryopreservation efficiency on embryo growth after exposing them in intracellular cryoprotectant ethylene glycol or glycerol and replacing them by trehalose - DATTA, ANUPAM; MAJUMDER, A C; BAG, SADHAN; DAS, SUKANTA; CHHETRI, RAJNI (The Indian Journal of Animal Sciences, 2018)
The present study was conducted to see whether toxicity could be reduced by replacing some of the penetrating cryoprotectant (intracellular cryoprotectant) with a disaccharide as well as finding out the optimum equilibration time in a vitrification solution before rapid cooling. Goat ovaries (1,685) were aspirated and 1,761 culturable oocytes (COC) were recovered. The recovered COCs were matured in maturation medium and evaluated on the basis of cumulus expansion. The matured oocytes were coincubated with fresh semen capacitated in TALP media, for 18 h. The inseminated oocytes were further cultured in mSOF for in vitro embryo development. The cleavage rate was 11.76% and the development rate of embryos to 4–8 and 8–16 cells morulae was 55.6% and 42.4%, respectively. In vitro produced goat embryos (132), 4–16 cell stages, were used for cryopreservation using different protocols. In protocol- 1, 2, 3 and 4, there was no survivability of embryos. In protocol- 5, 6, 7 and 8, the survivability of embryo after freezing was 10, 25, 35.7 and 72.2%, respectively. In protocol- 8, the percentage of live embryos was significantly higher than other protocols. Also it was found that the survivability rate of embryos in protocol 6 and 7 were significantly higher as compared to protocol 1, 2, 3, 4 and 5. However, non-significant differences were found among protocol 1, 2, 3, 4 and 5, and between 6 and 7. From our results, it can be concluded that cryopreservation using 20% ethylene glycol and 0.9 M trehalose for 30 min gives significantly higher post thaw (72.2%) survivability of embryos.